Lipopolysaccharide shock reveals the immune function of indoleamine 2, 3-dioxygenase 2 through the regulation of IL-6/stat3 signalling. Issue 1 (December 2018) - Yamamoto, Yasuko; Yamasuge, Wakana; Imai, Shinjiro; Kunisawa, Kazuo; Hoshi, Masato; Fujigaki, Hidetsugu; Mouri, Akihiro; Nabeshima, Toshitaka; Saito, Kuniaki
Abstract Indoleamine 2, 3-dioxygenase 2 (Ido2) is a recently identified catalytic enzyme in the tryptophan-kynurenine pathway that is expressed primarily in monocytes and dendritic cells. To elucidate the biological role of Ido2 in immune function, we introduced lipopolysaccharide (LPS) endotoxin shock to Ido2 knockout (Ido2 KO) mice, which led to higher mortality than that in the wild type (WT) mice. LPS-treated Ido2 KO mice had increased production of inflammatory cytokines (including interleukin-6; IL-6) in serum and signal transducer and activator of transcription 3 (stat3) phosphorylation in the spleen. Moreover, the peritoneal macrophages of LPS-treated Ido2 KO mice produced more cytokines than did the WT mice. By contrast, the overexpression of Ido2 in the murine macrophage cell line (RAW) suppressed cytokine production and decreased stat3 expression. Finally, RAW cells overexpressing Ido2 did not alter nuclear factor κB (NF-κB) or stat1 expression, but IL-6 and stat3 expression decreased relative to the control cell line. These results reveal that Ido2 modulates IL-6/stat3 signalling and is induced by LPS, providing novel options for the treatment of immune disorders.